The Source : A Novel - Michener, James A. (London Mandarin, 1994)
The story of Israel and all the Bible lands through many centuries. Into this massive canvas, James Michener has woven a constant thread, the story of man's spiritual pilgrimage amidst oppression and suffering.
English Fiction.
Keywords: Jews -- Israel -- Excavations (Archaeology)